CSR Failures in Bangladeshi Apparel Industry: An Agency Theory Perspective - Rahnuma Siddika; Sibbir Ahmad (International Journal of Supply Chain Management, 2022)
The apparel industry has a complex global supply chain that makes it difficult to monitor the Corporate Social Responsibility practices in the upstream firms. In recent years, the customers' sensitivity towards environmental, social, and worker safety has increased strikingly. In the last decade, several cases of apparel industry CSR failures in Bangladesh attracted global attention. CSR failure in any stage of the supply chain also damages the downstream firm's reputation and profitability. This study explores why the CSR practices in the fashion industry's global supply chain are susceptible to implementation failures, particularly in the Bangladeshi manufacturing industry, and how they could be mitigated. The findings from the cases this study went through explain that CSR failures in the supply chain negatively affect the reputation of the fashion brands in the downstream because consumers want to know more about the supply chain, where the products they are purchasing are coming from, who produces, and how; and they value the corporate social responsibly (CSR) practices in the supply chain. Therefore, implementing a good and sustainable CSR policy is a major concern of the companies. Information asymmetry and goal conflicts among the contracting parties (Principal and agent) lead to adverse selection, moral hazard, and hold-up problems in maintaining a standard CSR practice. This study delves into these issues through the lens of agency theory and shows that agency theory instruments can help mitigate the CSR failures of the Ready-Made Garments (RMG) industry in Bangladesh.